Analisis Perkawinan Sesuku di Desa Leuburi Kabupaten Lembata: Studi Pasangan Suami-Istri dalam Konteks Budaya dan Adat - Maria Valentina; Juliana Susantje Ndolu; Chatryen M. Dju Bire (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to examine the implementation of customary law governing same-clan marriage (aman udeq), community perceptions, and its social and cultural implications in Leuburi Village, Buyasuri District, Lembata Regency. The research employed an empirical legal method with a qualitative approach. Primary data were collected through in-depth interviews with 18 informants consisting of customary leaders, the village head, three same-clan married couples, family members, and community representatives. Secondary data were obtained from statutory regulations, legal literature, and relevant scholarly publications. The findings indicate that same-clan marriage remains strictly prohibited under the customary exogamous kinship system practiced by the Leuburi community. Enforcement of customary law is carried out through genealogical verification, customary deliberation, and the imposition of sanctions, including revocation of clan membership, social exclusion, customary reconciliation ceremonies, restriction of customary rights, and the non-recognition of descendants within the customary lineage. Most community members continue to uphold this prohibition as an effort to preserve cultural values and kinship order, although limited alternative views have emerged due to emotional factors and ongoing social change. The study concludes that customary law continues to play a significant role in maintaining social order while adapting to the challenges of modernization.